Spectrum and short-term outcome of acute kidney injury in renal allograft recipients: A single-center experience of Northwest India - Shyam Sundar Nowal (Indian Journal of Transplantation, 2020)
Introduction: Acute kidney injury (AKI) episodes in postrenal transplant are important determinants of short- and long-term graft survival. Renal allograft recipients (RARs) are more vulnerable for AKI and differ in risk factor, etiology, and outcome compared to community-setting AKI. The aim of this study was to evaluate the spectrum and the impact of AKI episode on RARs. Materials and Methods: This was a single-center, prospective observational study on 72 RARs (live and cadaveric) with a total of 93 AKI episodes, who were admitted with AKI (as defined by Kidney Disease Improving Global Outcome [KDIGO] criteria) between October 2016 and September 2018 and were followed for 3 months after AKI episodes. Results: A total of 93 AKI episodes occurred in 72 RARs during the study period. The mean age was 36.32 ± 12.03 years and mean serum creatinine at AKI episode was 2.59 ± 0.85 mg/dl. The etiologies of AKI were infections (n = 67, 72.04%), biopsy-proven rejection (n = 10, 10.75%), calcineurin inhibitor toxicity (n = 9, 9.67%), biopsy-proven acute tubular necrosis (n = 3, 3.22%), recurrence of native kidney disease (n = 2, 2.15%), and miscellaneous causes (n = 2, 2.15%). The majority (n = 53, 57.98%) of AKI episodes developed in the 1st year of transplant, 14 (15.05%) between 1st and 2nd year posttransplant, while the rest 26 (27.95%) beyond 2 years. Sixty-nine (74.2%) AKI episodes were in the KDIGO Stage 1, 18 (19.4%) were in Stage 2, and 6 (6.5%) episodes were in Stage 3. At 3 months of follow-up, various factors associated with nonrecovery of renal functions, including multiple AKI episode (P = 0.006), AKI requiring dialysis (P = 0.027), AKI Stage II or III (P = 0.003), and noninfectious etiology (P = 0.027). Overall, AKI had significant impact on renal allograft function at 3 months (P = 0.045). Pulmonary infection (P = 0.016) and need for dialysis (P = 0.001) were associated with increased risk of mortality in RARs after AKI. Conclusion: AKI in RARs had significant impact on renal allograft function and recovery.